Clinical Features of Hypersensitivity Pneumonitis in Children: A Single Center Study - Zhang, Feizhou; Yang, Tongyu; Liu, Zhixuan; Jia, Xuan; Yang, Li; Wu, Lei; Tang, Lanfang (Frontiers in Pediatrics, 2022)
Background: Hypersensitivity pneumonia (HP) is an interstitial lung disease (ILD) mainly involving small airways and lung parenchyma that is caused by the inhalation of allergens in susceptible people to stimulate the body's immune response. Methods: A total of 6 Chinese children with HP treated in our center from July 2017 to July 2021 were included in our study. Results: Among the children, there were 4 males and 2 females, ranging in age from 4 to 14 years old. 3 cases had chest tightness and shortness of breath; 2 cases had cough; 1 case had chest pain and 1 case had fever. 2 cases of children had a history of close contact with pet dogs, 1 case had a history of contact with pigeons, 2 cases lived in moldy house recently, 1 case recently played a saxophone that had been idle for more than 2 years. The parents of two cases also had similar symptoms recently. The specific signs of chest HRCT of 6 cases all were in line with the characteristics of HP. After avoiding the sensitization environment, 2 children quickly recovered, 4 patients received low-dose glucocorticoid oral treatment, and after symptom control the dose was gradually reduced. The course of treatment was about 3-6 months. Conclusions: Exposure to a potential antigen has been found in all 6 HP children. The clinical manifestations are heterogeneous and easy to confuse with other diseases. A clear history of exposure to the allergen, respiratory symptoms associated with HP, signs of HP on HRCT, and improvement after removal from the allergen environment constitute the cornerstone of the diagnosis of HP children in our unit. Avoiding exposure to antigen environment is the first step in treatment, and glucocorticoid use is necessary in children with persistent symptoms.